Efeitos de dimensionalidade em perovskitas de haletos para aplicações em células solares: um estudo ab initio - Almeida, João Gabriel Danelon Vieira de (2022)
The structural stability and toxic lead are known obstacles to the current photovoltaic application of perovskite solar cells (PSCs) with high power conversion efficiencies (PCEs). Herein, we perform a systematic study contrasting structural, energetic and optoelectronic properties of 3D and 2D perovskites by substituting metal and halide compositions, and estimating the maximum PCE of these systems. Our investigation was performed with ab initio density functional theory calculations as implemented in the VASP (Vienna ab initio simulation package) code. We investigate 3D MABX3 perovskites with a 2x2x2 supercell and 2D (BA)2(MA)B2X7 (B = Ge, Sn, Pb, X = Cl, Br, I) structures with two octahedral layers. The inclusion of the organic spacer molecules is observed to change the distortions inside the octahedra and weaken the Jahn-Teller effect, as the effective coordination number for the B atom goes from 3.67 NNN to 5.16 NNN (NNN, number of nearest neighbors) considering 3D and 2D GeI-based materials. The BA molecules also provide a greater distortion between octahedra, with angles between B-X-B atoms presenting values in average 5º smaller than the bulk materials, which is a important factor as these distortions are known to affect the electronic band gap. Contrasting the stability of 3D and 2D perovskites, we observed that the presence of organic spacers on the 2D structure increases the cation/anion charge separation, which produces stronger Coulomb interactions resulting in a better stability. Our PCE estimates resulted in 8 perovskite combinations with values over 27% considering both 3D and 2D structures with BX = GeI, SnBr, SnI and PbI. Moreover, the 2D perovskites reached maximum PCEs with a 3.5x narrower layer thickness than 3D perovskites, envisioning a substantial fabrication cost reduction. Furthermore, the PCE estimate for (BA)2(MA)Sn2I7 showed an excellent result of 32.40%, a higher value than its 3D analogous MASnI3 with 27.63% and also higher than the 29.90% value for MAPbI3. The obtained results reinforce the better stability of 2D PSCs and can suggest promising materials with high PCE and without the toxicity of Pb.